The Effect of Mental Health and Job Satisfaction on Employees Work Morale at Pt. Bank BPR Kerta Raharja Majalaya Branch - Lucky Krisna Wijaya; Inne Satyawisudarini; Puti Harissa Pratidhina; Ani Yunaningsih (Business Management, 2026)
This study aims to analyze the influence of mental health and job satisfaction on employee morale at PT. Bank BPR Kerta Raharja Majalaya Branch. This research is motivated by the increasing work pressure in the banking industry, especially in Rural Banks (BPR), which requires employees to work productively, adaptively, and possess strong psychological resilience. This study employed a quantitative approach using descriptive and verification methods. Data collection was conducted through questionnaires distributed to employees of PT. Bank BPR Kerta Raharja Majalaya Branch. Data analysis was carried out using multiple linear regression analysis to determine the partial and simultaneous effects of mental health and job satisfaction on employee morale. The results indicate that mental health and job satisfaction have a positive and significant effect on employee morale.